A swift risk analysis for COVID-19 testing facilities using rapid tests - VOURTSIS, Dionysios; PAPAGEORGIOU, Efstahia; KRIEBARDIS, Anastasios; KARIKAS, George Albert; WILLIGEN, Gijsbert van; KARKALOUSOS, Petros (One Health & Risk Management, 2022)
Introduction: COVID-19 is an infectious disease of International Concern, due to the widespread geographic impact and high transmissibility, causing severe illnesses. The quick detection of cases and isolating them has become very crucial, therefore many testing facilities were set-up for monitoring the spread of the SARS-COV-2 virus, at the early days of the coronavirus pandemic. From Biosafety aspect this study investigates a reliable risk assessment method to identify and mitigate the risks of COVID-19 testing facilities using Rapid diagnostic tests (POCT), in order to protect the staff, the people who got tested, the community and the environment.Material and methods: Many techniques have been used so far for performing a risk assessment. In the present study, SWIFT analysis suitable for biosafety facilities and for risks of different magnitude, was used for identifying threats and hazards and to calculate the risks for COVID-19 testing facilities.Results: Our analysis showed several initial and potential risks, which could lead to unwanted exposure or release of the SARS-COV-2, and/or unwanted infection of staff and patients. With minor adjustments of the testing facility, by creating standard operating procedures and awareness of the potential risks, most of the identified risks could be mitigated.Conclusions: Our study demonstrated that when setting up a COVID-19 testing facility, a proper risk assessment should be part of the process, in order to ensure the safety of staff, patients, and the environment. Additionally, we proposed a number of multiple mitigation measures and recommendations, with the goal to reduce the risks during the rapid testing diagnostic procedure.